Effect of nano- and micro-polystyrene particles on small intestinal epithelial functions and enteric neuronal activity in vitro - Kristin Elfers; Pascal Benz; Marion Burmester; Silja Hein; Kathrin Hansen; Holger Sieg; Linda Böhmert; Maxi B. Paul; Gemma Mazzuoli-Weber (Microplastics and Nanoplastics)
Abstract Based on their ubiquitous distribution in various ecosystems, plastic particles of different origin and sizes enter the (human) food chain, are ingested and reach the gastrointestinal tract, where they interact with the intestinal (epithelial) tissue. To a certain extent, they may enter or cross the intestinal epithelium, getting into contact with enteric neurons. Therefore, a potential risk for gastrointestinal health has been suggested. In the current study, we aimed to investigate the effect of polystyrene particles of nano- (100 nm) and micro-size (1.0 μm), firstly, on intestinal epithelial electrophysiological processes using the Ussing chamber technique and, secondly, on enteric neuronal properties using neuroimaging on primary cultured enteric neurons. The results indicate a size-dependent impairment of epithelial integrity and electrogenic glucose transport upon particle application. Additionally, both sizes of particles induced a change in neuronal response parameters to nicotinergic stimulation after a 24 h incubation. Taken together, these results emphasise the potential of nano- and micro polystyrene particles to interact and affect intestinal epithelial as well as enteric neuronal functionality and stress the need for more detailed investigations of the effect of plastic particles present in the (human) diet on intestinal physiology and involvement of the enteric nervous system.